Settlement‐era forest structure and composition in the Klamath Mountains: reconstructing a historical baseline. Issue 9 (18th September 2020) - Knight, Clarke A.; Cogbill, Charles V.; Potts, Matthew D.; Wanket, James A.; Battles, John J.
Abstract: Historical baselines of forest conditions provide reference states to assess how forests have changed through time. In California, the Public Land Survey System (PLSS) provides tree inventory data between 1872 and 1884 at 93.2‐km 2 (36 mi 2 ) resolution. Although these data provide a spatially extensive record of settlement‐era forest conditions, reconstructions using PLSS data have been limited and controversial in western landscapes. Recent improvements in the application of plotless density estimators (PDE) have made reconstructions more accurate and robust. The purpose of this study was to use PDE to reconstruct the settlement‐era forest conditions in Six Rivers National Forest—a floristically diverse temperate forest in the Klamath Mountains of northwestern California—to quantify differences with modern conditions. Records of fires and harvests were used in conjunction with the PLSS data to understand the influence of forest management during the previous century. The contemporary forest in Six Rivers contains three times more trees than in the settlement era with a comparable increase in tree basal area. Forest composition during the settlement era was predominantly Douglas‐fir (34.4%), pine (24.2%), and oak (21.9%) by basal area. Contemporary forests support more Douglas‐fir (45.2%) and a similar amount of pine (26.1%), while oaks have decreased by more than half (9.3%). These increases in tree abundance occurred despite extensive, mid‐century timber harvesting in Six Rivers. Although large fires have burned in Six Rivers between 2000 and 2019, far fewer fires occurred during the twentieth century. Our results suggest that effective fire suppression contributed to the densification of the contemporary forests in Six Rivers.